Experimental investigations on micro machining of high speed steel using WEDG. (24th April 2019) - Krishnaraj, V.; Parthiban, M.; Sindhumathi, R.
This paper reports the effects of machining parameters on material removal rate, surface roughness and circularity in cylindrical wire electric discharge grinding (WEDG) of high speed steel. A rotary axis spindle is set up in the wire electric discharge machine in a submerged dielectric environment so as to machine cylindrical parts. The speed of the rotary axis spindle is maintained constant at 200 rpm. Experiments have been carried out under different process conditions like pulse current, open circuit voltage, pulse off time, servo voltage and number of passes. To obtain the best surface quality, the most significant parameters were identified. From the optimised wire electric discharge grind process micro pins were manufactured.